ZNACZENIE I ROLA ŚWIADKÓW W LEGALIZACJI WCZESNOŚREDNIOWIECZNYCH DOKUMENTÓW NA PRZYKŁADZIE WYBRANYCH DOKUMENTÓW ZAKONU TEMPLARIUSZY - Streit, Henryk (In Gremium. Studies in History, Culture and Politics, 2019)
THE ROLE AND IMPORTANCE OF THE WITNESSES OF THE LEGALISATION OF THE EARLY MIDDLE AGES’ RECORDS ON THE BASIS OF THE KNIGHTS TEMPLAR’S DOCUMENTS S u m m a r y This article describing the issue of the witnesses and their functions in the process of legalization of medieval documents also aim to show the rightness of the opinions about the authenticating functions of testators created in the diplomatic doctrine. It also indicates that the very fact of the increase of the lawful role of a stamp on the turn of the 13 the century does not allow to completely reject the list of witnesses as one of the means of authenticating a document coexisting with the stamp. The analysis of a group of documents of an order of templars dated back to the years between 1232-1308 seems to support the above-mentioned conclusions. Tłum. Henryk Streit